2013
DOI: 10.1001/jama.2013.282081
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Communication Skills Training for Residents and Nurse Practitioners on Quality of Communication With Patients With Serious Illness

Abstract: IMPORTANCE Communication about end-of-life care is a core clinical skill. Simulation-based training improves skill acquisition, but effects on patient-reported outcomes are unknown.OBJECTIVE To assess the effects of a communication skills intervention for internal medicine and nurse practitioner trainees on patient-and family-reported outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
230
3
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(257 citation statements)
references
References 43 publications
13
230
3
5
Order By: Relevance
“…[15][16][17][18] The differences between the measures used in this study versus previous research may help explain the differences. Further, the students in this study participated in five cases over five weeks.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…[15][16][17][18] The differences between the measures used in this study versus previous research may help explain the differences. Further, the students in this study participated in five cases over five weeks.…”
Section: Discussionmentioning
confidence: 83%
“…[15][16][17][18] Recent comparative research has shown that RP/CS may be just as effective at teaching communication as SP and at a lower cost to the institution. Further, simulation with SPs requires significant time on the part of faculty members who wish to incorporate SPs into teaching and assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This randomized trial of a simulation-based communication skills-building workshop for IM residents, subspecialty fellows, and nurse practitioners assessed effects on patient-, family-, and clinician-reported outcomes. 13 In a prior study, this workshop was associated with significant improvements in communication skills with regard to giving bad news and responding to emotion, assessed using SP encounters. Of 1,068 eligible trainees from two academic medical centers, 44 % were randomized to the intervention workshop, consisting of eight 4-hour sessions, versus controls who were provided standard education.…”
Section: Resultsmentioning
confidence: 93%
“…This study is limited by its small, although varied, sample and precludes definitive conclusions. It is unclear whether the nature of communication for families with seriously ill children has significantly changed since the time of these deaths [18]. Moreover, the relationship between memories and quality of care or patient satisfaction is unknown.…”
Section: Discussionmentioning
confidence: 99%